Peer-Supported Informal Learning in Esports: An Analysis of Mobile Legends YouTube Tutorial Comments - Virgi Perdana Kusuma; Dian Permata Sari (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study examines how YouTube comment spaces attached to Mobile Legends tutorial videos contain observable traces of peer-supported informal learning. Using an exploratory mixed-method design, the study analyzed 3,805 cleaned public comments collected from 32 Indonesian-language tutorial videos across 15 channels. Data were examined through codebook-based educational content analysis, supported by descriptive thematic mapping of gameplay topics and interaction tone. The codebook focused on questioning, clarification, experience sharing, peer advice, learning evaluation, and learning difficulty; coding credibility was addressed through expert review, pilot coding, and intercoder reliability reporting. The findings show that 1,156 comments (30.38%) contained explicit informal learning indicators, while 206 comments (5.41%) expressed learning difficulties. Questioning was the most visible learning act, and the most frequent difficulty concerned transferring tutorial knowledge into actual matches. The study contributes by reframing YouTube comments as observable educational traces rather than simple engagement indicators. Practically, the findings suggest that tutorial creators can use comment patterns to design more scaffolded, conditional, and practice-oriented explanations.